The Use of Corn Husks Through Storytelling Techniques to Develop Children's Character - Siti Rondiyah; Endang Dewi Murrinie; Fitri Budi Suryani (Journal of Psychology and Instruction, 2022)
The learning process does not lead to character education, so the child's character needs to be improved. The lack of interesting learning media development is because teachers use monotonous learning media. There are no learning innovations that can attract children's interest. This research aims to create interesting storytelling media using corn husks to build children's character to be better and have good morals. This type of research is R & D research, with this research method referring to the theory of Borg and Gall, which consists of ten steps of research implementation. Research subjects with 15 students as the experimental and five as the control classes. Data collection techniques used were interviews, observation, and questionnaires. The analysis used in this research is quantitative and qualitative. The results of developing media using corn husks through storytelling techniques based on the validation of material experts and media experts are feasible for building polite, honest, and disciplined characters in children. Media development using corn husks through effective storytelling techniques is used to build polite, honest, and disciplined characters in Kindergarten Group B children with a t-test of 21,189 and a t-table of 4,381 or 21,189 more than 4,381. At the same time, the N-Gain score is 71 in the effective category.